2015
DOI: 10.1016/j.visres.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the utility of visual acuity measures in visual prostheses

Abstract: There are presently several ongoing clinical trials to provide usable sight to profoundly visually impaired patients by means of electrical stimulation of the retina. Some of the blind patients implanted with retinal prosthesis reported un-patterned perception and yet benefit from the device in many activities of daily living, seemingly because they adopt active scanning strategies. The aim of the present work is to evaluate if and under what conditions a measured visual acuity level is truly an indication tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Firstly, we were able to eliminate the contributions of head scanning to localization, as head scanning can increase the acuity provided by the device over that of the physical limit imposed by the geometric spacing between electrodes. 10 We were also able to eliminate other factors such as nonvisual information that can influence performance with prosthetic vision. 11 Lastly, performance using different stimulation strategies could be directly compared with a high degree of stimulus repeatability.…”
Section: Static Image Localizationmentioning
confidence: 99%
“…Firstly, we were able to eliminate the contributions of head scanning to localization, as head scanning can increase the acuity provided by the device over that of the physical limit imposed by the geometric spacing between electrodes. 10 We were also able to eliminate other factors such as nonvisual information that can influence performance with prosthetic vision. 11 Lastly, performance using different stimulation strategies could be directly compared with a high degree of stimulus repeatability.…”
Section: Static Image Localizationmentioning
confidence: 99%
“…Given the prostheses' limited field of view, users may learn to use head movements to scan along or trace across the contours of objects. Indeed, Caspi and Zivotofsky (2015) found that subjects were able to discriminate low resolution, non-patterned images of the four alternative Landolt C acuity targets using head scanning or tracing. Motor tracing may also be used to produce correct word recognition responses, since the use of large font sizes (da Cruz et al 2013a, Grant et al 2016) or the use of the prosthesis camera's zoom capability (Nau et al 2014a, Grant et al 2016 allows motor tracing along the high contrast letter strokes (da Cruz et al 2013a(da Cruz et al , 2013b.…”
Section: Discussionmentioning
confidence: 99%
“…The primary purpose of evaluation is to determine if a device provides pattern vision (Caspi and Zivotofsky 2015) with similar spatial and temporal characteristics to the normal human visual system. A normal visual system is capable of learning spatial patterns and it can generalize from training to novel stimuli and contexts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations